Exploring new bioprocess considerations for cardiomyogenesis of embryonic stem cells - Teo, Ailing (2014)
Ex vivo cardiomyocytes production from pluripotent stem cells is highly attractive as a future clinical therapy for cardiovascular diseases. Scaled-up 3-dimensional cell culture can be used to produce clinically relevant cell numbers but requires numerous bioprocess design considerations. In this thesis, we employed hydrogel encapsulation of mouse embryonic stem cells (mESCs) to study various novel design parameters that could be used for large-scale cardiomyocyte production. First, we demonstrated that our novel rotary, perfused bioreactor provided a dynamic and perfused environment that was superior to a commercial rotary wall bioreactor and conventional tissue culture vessels in terms of cell numbers and cardiac differentiation. With this novel bioreactor, we had also investigated the effects of pH on cardiomyogenesis. Cardiomyogenesis was found to be sensitive to different pH values, where slight fluctuations could cause significant changes to cell proliferation and cardiac differentiation. Last but not least, we utilised ultrasound as a novel mechanical stimulus for cardiac differentiation of mESCs and demonstrated its benefits in improving cardiomyocyte yield.